Neglected cardiovascular risk factors: Relationship of anxiety and depression with percutaneous coronary angioplasty - Hadi, Mohd Firdaus; Shenq, Kelvin Woei Siew; Mohd Firdaus, Mohd Al-Baqlish; Mohammad Aidid, Edre; Wei, Sylvia Wei Kong; Zainal Abidin, Imran (SAGE Publications, 2021)
Introduction: Coronary artery disease (CAD) is the leading cause of mortality in Malaysia. Psychological risk factors are associated with detrimental outcomes in CAD. Our study aimed to evaluate procedural anxiety and depression levels among subjects who underwent coronary angioplasty.